hydrogeology, hydrochemistry and stable isotopes in the Ouémé Delta, southern Benin - Alassane, Abdoukarim; BOUKARI, MOUSSA; MAMA, DAOUDA (My University, 2023)
The Mio-Pliocene aquifer of the coastal sedimentary basin of Benin is the most exploited aquifer for water supply to the urbanised region in the southern part of the country. The population explosion is putting increasing pressure on quantitative and qualitative aspects of the groundwater resources. Preventing groundwater contamination caused by surface waters requires a thorough understanding of surface-water/groundwater interactions, especially the interactions between the Mio-Pliocene aquifer and surface waters. This study aimed to investigate the interactions between groundwater and surface waters along the major rivers (Sô River and Ouémé Stream) and brooks in the Ouémé Delta. Field campaigns identified 75 springs located in the valleys which feed the rivers, and thus maintain their base flow. The piezometric results indicated, through flow direction assessment, that the Mio-Pliocene aquifer feeds Ouémé Stream and Sô River. Chemical analyses of groundwater and surface waters show similar chemical facies, and changes in the chemical composition in groundwater are also observed in the surface waters. Moreover, the isotopic signatures of surface waters are similar to those of the groundwater and springs, which led to the identification of potential groundwater discharge areas. As a result of groundwater discharge into surface waters, the fraction of groundwater in the surface water is more than 66% in the brooks, regardless of the season. In the Ouémé Stream and Sô River, the fraction of groundwater is 0–21% between June and September, while from October to March it is 47–100%.
Keywords: Groundwater/surface-water relations · Stable isotopes · Benin